Controlling the composition, phase volume, and viscosity of microemulsions with cosolvent. (1st January 2018) - Tagavifar, M.; Jang, S.H.; Chang, L.; Mohanty, K.; Pope, G.
Graphical abstract: Abstract: Optimizing macroscopic properties of microemulsions (volume, composition, and viscosity) is tedious and often involves the use of an alcohol. We show that this optimization is possible when the alcohol acts as cosolvent (rather than a cosurfactant) to partition between the interface and bulk phases(s). Herein presented a phase behavior study of water, crude oil, tridecyl alcohol propoxy sulfate (C13 -13PO-SO4 ), internal olefin sulfonate (C20-24 IOS), and ethoxylated phenol (phenol-2EO) mixtures, rationalized by pseudophase theory and pseudoternary phase diagram. The detailed phase behavior study involved varying the surfactant concentration, cosolvent concentration, brine salinity, and oil content. High-performance liquid chromatography (HPLC) was used to determine the interfacial composition and steady and dynamic rheology to characterize the bicontinuous middle-phase samples. Measurements confirmed that phenol-2EO acted as cosolvent. A systematic shift of phase type is observed by increasing the cosolvent-to-surfactant content in the initial water/surfactant solution. Furthermore, it was observed that the interfacial ratio of cosolvent to surfactant controls the microemulsion composition, viscosity, and volume. This ratio is highly tunable, but when too high, a distortion of the middle phase is observed. The experimental results provide a methodology to tailor the composition of amphiphile mixture for optimizing microemulsion properties.